ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN PADA PT GINTING JAYA ENERGI. Tbk - Rina Nababan; Sondang Tampubolon; Esma Sinaga (CV. Denasya Smart Publisher, 2025)
This study analyzes the financial performance of PT. Ginting Jaya Energi, Tbk using financial ratios, including profitability, liquidity, and solvency ratios, during the period 2020-2023. The data used are the annual financial statements of the company listed on the Indonesia Stock Exchange, analyzed descriptively quantitatively using the horizontal comparison method. The analysis results show that profitability ratios, such as Return on Investment (ROI) and Return on Equity (ROE), tend to be negative, indicating the company's difficulty in generating profits from investments and equity. Meanwhile, liquidity ratios such as Current Ratio and Quick Ratio, indicate the company's good ability to meet short-term obligations. Solvency Ratios, such as Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), are below industry standards, indicating that the company does not rely too heavily on debt. This research provides important insights for investment considerations and managerial improvements for the company.